SOME PROPERTIES FOR HIGHER ORDER COMMUTATORS OF HARDY-TYPE INTEGRAL OPERATOR ON HERZ-MORREY SPACES WITH VARIABLE EXPONENT - Akin, Lutfi; Zeren, Yusuf (YILDIZ TECHNICAL UNIV, 2019)
In this work, the boundedness for higher order commutators of Hardy-Type integrals is obtained on HerzMorrey spaces with variable exponent M(K)over dot(p,q(.))(beta(.)lambda) (R-n) applying some properties of variable exponent.
Keywords: Variable exponent; hardy-type integral; Herz-Morrey space; FRACTIONAL INTEGRALS; BOUNDEDNESS; FUNCTIONALS; LEBESGUE; Engineering